Critical Thinking Skills and Physics Learning Outcomes in The 5E Learning Cycle Model with PhET Simulations - Rifqoh Putri Purfiyansyah; Singgih Bektiarso; Lailatul Nuraini (Universitas Negeri Padang, 2023)
This research aimed to examine: (1) the significant effect of the 5E learning cycle model with PhET simulations on students' critical thinking skills; and (2) the significant effect of the 5E learning cycle model with PhET simulations on students' physics learning outcomes. The type of this research was true experimental with a post-test only control group design. The population of this research was students eleventh science grade of senior high school Balung in the even semester of the 2021/2022 academic year. The sample was determined using a simple random sampling method to obtain a selection of first science class as the experimental class and second science class as the control class. Data collection techniques include tests, interviews, documentation, and observation. Data analysis used is homogeneity test, normality test, and hypothesis test. The results of this research were: (1) there is a significant effect of the 5E learning cycle model with PhET simulations on students' critical thinking skills; and (2) there is a significant effect of the 5E learning cycle model with PhET simulations on students' physics learning outcomes.